Pengaruh Kualitas Produk dan Harga Terhadap Kepuasan Konsumen Selama Pandemi Covid-19 Pada Kamsia Boba Teluk Betung - Tri Lestira Putri Warga Negara; Davin Ang Widjaya (Jurnal Widya, 2022)
The purpose of this study was to determine whether product quality and price simultaneously affect consumer satisfaction at Kamsia Boba Teluk Betung. The survey results community is that Kamsia Boba's customers have purchased food in 2020 as many as 63,415, with the slovin formula, the sample size was found to be 100 people. The method of analysis using Multiple Linear Regression analysis, determination coefficient test, partial hypothesis testing and ANOVA hypothesis testing. From the research, it was found that product and price greatly affect consumer satisfaction at Kamsia Boba Teluk Betung, proven and acceptable truth. It is hoped that with this research Kamsia Boba Teluk Betung maintains the stability of the quality of both products and for customers. Thus being able to increase customer satisfaction at Kamsia Boba Teluk Betung.